P218 Prospective study of primary cough headache in a cough unit. (12th November 2019) - Moreno Ajona, D; Cho, P; Becker, S; Hoffmann, J; Goadsby, PJ; Birring, S
Abstract : Objective: Description of the characteristics, prevalence and comorbidities associated with cough headache in a cough unit. Methods: From July 2018 to present time, consecutive patients who attend the Cough Clinic were asked about the presence of headache with and without cough. The eligibility of the participants was determined through a telephone interview. Neurological and neuro-otological examination; the modified Valsalva manoeuvre were completed, and MRI with cranio-cervical views. Results were tabulated and statistical analysis included χ2 and Pearson correlation coefficient. Results: At interim analysis, 245 patients completed the initial screening. Of these, 167 (68%) suffered from headache, of which 78 (47%) reported headache with cough. Fifty patients have completed the telephone interview (61% women, mean age of 45±4 years) and 35 (70%) met the diagnostic criteria of cough headache according to the International Classification of Headache Disorders (ICHD-3). The remaining patients met the criteria for migraine. Among patients with cough headache, 90% had a previous history of migraine. Mean time since headache onset was 7 years (range 3–11 years). The average attack duration was 1 hour, the most frequent location was occipital and cough was the only trigger in 65%. Associated symptoms included vertigo or 'lightheadedness' for seconds in 52% of patients. The modified Valsalva manoeuvre was positive in 37% but did not distinguish between primary and secondary headaches. The respiratory diagnosis: chronic cough after exclusion of asthma, post nasal drip, and reflux disease, was significantly related to the diagnosis of cough headache (χ2=5.2 p =0.02). Four cases (8%) of secondary headaches were identified: Chiari malformation, fungal sinus infection and headache attributed to low CSF pressure. Conclusion: In the presence of chronic cough, primary cough headache is more frequent in women with a history of migraine. Secondary cough headache was not as prevalent as in previous series. The modified Valsalva test was not capable of distinguishing primary from secondary headaches.